Anti-Americanism in Latin America and the Caribbean - McPherson, Alan L. (Explorations in culture and international history series, 2006)
"This book brings leaders in the field of U.S.-Latin American relations together with the most promising young scholars to shed historical light on the present implications of hostility to the United States in Latin America and the Caribbean. In essays that carry the reader from Revolutionary Mexico to Peronist Argentina, from Panama in the nineteenth century to the West Indies' mid-century independence movement, and from Colombian drug runners to liberation theologists, the authors unearth little known campaigns of resistance and probe deeper into episodes we thought we knew well. They argue that, for well over a century, identifying the United States as the enemy has rung true to Latin Americans and has translated into compelling political strategies. Combining history with political and cultural analysis, this collection breaks the mold of traditional diplomatic history by seeing anti-Americanism through the eyes of those who expressed it. It makes clear that anti-Americanism, far from being a post-9/11 buzzword, is rather a real force that casts a long shadow over U.S.-Latin American relations."--Book jacket.